ANALISIS KONSEP PENYUSUNAN INSTRUMEN PENILAIAN KOGNITIF DIAGNOSTIK YANG RESPONSIF TERHADAP PERBEDAAN KEBUTUHAN BELAJAR SISWA SD - Novita Sari, Dwi; Adira, Hukma Fikria; Lestari, Futry Ayu; Shaleh, Shaleh (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to analyze the development of cognitive-diagnostic assessment instruments that are responsive to differences in elementary students’ learning needs through a systematic literature review using the PRISMA 2020 approach. From an initial 300 articles, ten selected studies were analyzed in depth to examine theoretical foundations, development procedures, validity, reliability, and the responsiveness of instruments to variations in students’ cognitive abilities. The synthesis results indicate that effective diagnostic instruments generally emphasize the detection of misconceptions, conceptual understanding, and reasoning processes through the use of multi-tier formats, digital assessment, and adaptive approaches. Several studies reported that valid and reliable instruments improve teachers’ diagnostic accuracy and support differentiated instruction. However, challenges remain, including low discrimination power of certain items, limited classroom implementation, and suboptimal integration of assessment results into follow-up instructional strategies. In conclusion, the findings highlight the need for a more adaptive, comprehensive, and contextually relevant conceptual model of assessment instruments aligned with current learning demands.